Surface treatment method for high peel strength self-lubricating liner for spherical plain bearing
By using MAX material and shot peening on the pads of self-lubricating joint bearings, and combining the bonding technology of phenolic resin, the problem of poor bonding between the pads and the outer ring of the bearing is solved, and the bonding effect and service life are significantly improved.
Patent Information
- Application Number
- CN202411979303.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The failure of self-lubricating joint bearings is often caused by the insufficiency of bonding between the pad and the outer ring of the bearing, resulting in lubrication failure.
The bonding effect between the liner and the outer ring of the bearing is enhanced by shooting peening and the use of phenolic resin as the adhesive.
It significantly improves the bonding effect between the liner and the outer ring of the bearing, prevents falling off, extends the service life, and allows re-adhesion after stripping the liner, continuing the use of the bearing.
Smart Images

Figure CN119393460B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a surface treatment method, in particular to a surface treatment method for a high peeling strength self-lubricating liner for a spherical bearing. Background Art
[0002] Self-lubricating spherical bearings are special spherical bearings that do not require lubricant to be added during operation. A layer of self-lubricating material with anti-friction and wear-resistant properties is pasted or coated on the inner surface of the spherical bearings. Therefore, self-lubricating spherical bearings are mainly used in various motion systems such as aircraft landing gear systems and helicopter rotor systems in the aviation field. They are one of the most important parts. In the aerospace field, self-lubricating spherical bearings are used in important systems such as satellites and space station doors and robotic arms. When self-lubricating spherical bearings perform different movements, the friction between the original outer ring and inner ring of the bearing is replaced by the friction between the steel ring and the liner, so that the bearing no longer relies on grease to reduce friction, and the self-lubricating effect also breaks through the limit of the original oil film lubrication. Good lubrication can be achieved under various special working conditions, such as high speed and light load, low speed and heavy load, and compound swing. Good oil film lubrication is usually not possible under these working conditions, and maintenance-free spherical bearings can also be achieved.
[0003] Among the self-lubricating spherical bearings, self-lubricating spherical roller bearings are widely used in high-precision fields because of their lubrication method. On the one hand, it is because they can complete various different movements; on the other hand, their lubrication method saves the trouble of traditional bearings that need to constantly add lubricants during work. The addition of self-lubricants brings about the effect of self-lubrication and greatly improves work efficiency. In the research of self-lubricating related technologies, the research on self-lubricating layers occupies a very important position, because the performance of the self-lubricating layer often directly determines the performance and service life of the entire self-lubricating spherical bearing. At present, the self-lubricating layer of self-lubricating spherical bearings used in various fields is mainly a fabric-type liner, which is usually mixed with polytetrafluoroethylene (PTFE) and various other high-performance fibers, assembled into various structures, and then cured and coated with adhesives, and then bonded to the inner surface of the bearing of the outer ring of the spherical bearing through multiple processes.
[0004] However, since the friction between the outer ring and the inner ring of the spherical plain bearing is transferred to the liner, the failure of the self-lubricating spherical plain bearing is usually caused by the failure of the liner. In addition, most of the liner failures are not caused by the failure of lubrication between the liner and the inner ring, but by the liner falling off due to the poor adhesion between the liner and the outer ring of the spherical plain bearing. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a surface treatment method for a high peel strength self-lubricating liner for a spherical bearing, which makes the bonding between the liner and the outer ring of the spherical bearing more firm.
[0006] To achieve the above purpose, the technical solution of the present invention is as follows: A method for treating the surface of a high peel strength self-lubricating liner for a spherical bearing, wherein the liner surface is treated and installed on the outer ring of the spherical bearing according to the following steps:
[0007] S10, selecting MAX material as reinforcing particles of the liner, dissolving the MAX material in a precursor solution, immersing the liner in the precursor solution, and drying overnight to adhere the MAX particles to the surface of the liner;
[0008] S20, performing shot peening treatment on the bonding surface between the bearing outer ring and the liner;
[0009] S30, adding adhesive between the liner and the bearing outer ring, and curing the liner and the bearing outer ring after the bonding treatment.
[0010] Furthermore, there is a step S25 between steps S20 and S30, and the step S25 includes the following steps:
[0011] S25.a, diluting the adhesive with a diluent;
[0012] S25.b, adding the two-dimensional material to the mixed solution and stirring evenly;
[0013] S25.c, completely immersing the liner treated in step S10 in the solution obtained in step S25.b, so that the solution obtained in step S25.b penetrates the surface of the liner to obtain a two-dimensional material @MAX liner;
[0014] S25.d, using a roller press to remove excess resin from the surface of the two-dimensional material @MAX liner, and then drying at a temperature of 50-150° C. until the surface of the two-dimensional material @MAX liner is removed and the solution obtained in S25.b remaining on the surface is removed;
[0015] S25.e, repeat steps S25.a-S25.d to increase the weight of the 2D material @MAX pad by 30-60%. At this point, the thickness of the 2D material @MAX pad is 0.2-0.6 mm.
[0016] Furthermore, the adhesive in steps S25.a and S30 is phenolic resin; the diluent in step S25.a is a mixed solution of ethyl acetate and anhydrous ethanol or a mixed solution of ethyl acetate, anhydrous ethanol and acetone.
[0017] Furthermore, the mass fraction of the two-dimensional material in S25.b is 0.2-2%.
[0018] Furthermore, the curing process of step S30 is as follows:
[0019] S30.a, bonding the two-dimensional material @MAX liner processed in step S25 to the surface of the outer ring of the bearing;
[0020] S30.b, apply 0.1-5MPa pressure and control the temperature at 150-250°C until the bonding is stable, at which point the thickness of the 2D material @MAX pad is 0.2-0.7mm.
[0021] Furthermore, the precursor solution in step S10 is a mixed solution consisting of Tris (tris(hydroxymethyl)aminomethane) buffer, deionized water, catecholamines and polyvinylamine reagents.
[0022] Furthermore, the mass ratio of the precursor solution is as follows: the mass ratio of catecholamine & polyvinylamine reagent mixed solution: MAX is in the range of 8:1-2:1.
[0023] Furthermore, in the step S20, the particle size of the steel shot used for shot peening is 0.1-1 mm, and the shot peening pressure is 0.1-5 MPa.
[0024] Furthermore, the MAX material is titanium carbide aluminum.
[0025] In the above scheme, MAX material refers to Mn+1AXn phase material.
[0026] The beneficial effect of the present invention is that by shot peening the bearing outer ring and attaching reinforcing particles to the surface of the liner, the bonding effect between the bearing outer ring and the liner can be effectively improved to prevent the liner from failing due to separation from the bearing outer ring.
[0027] Secondly, the MAX particles are dissolved in a precursor solution and the liner is immersed therein, thereby enhancing the adhesion between the MAX particles and the surface of the liner.
[0028] Furthermore, after the liner is bonded to the bearing outer ring, even if the liner is peeled off, the bearing outer ring bonding surface will not be worn, thereby providing the possibility of bonding a new liner again to continue using the old bearing outer ring.
[0029] In addition, by using phenolic resin as an adhesive and a mixed solution of ethyl acetate and anhydrous ethanol or ethyl acetate, anhydrous ethanol and acetone as a diluent, the phenolic resin can be diluted by the mixed solution to prevent it from being too viscous to be applied, and the two-dimensional material can be fully dissolved in the diluent so that it adheres to the backing paper. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The metallographic morphology of the bonding surface between the outer ring of the bearing and the liner after shot peening in the embodiment of the present invention;
[0031] Figure 2This is the surface metallographic morphology of the MAX@PTFE / Kevlar liner of the embodiment of the present invention;
[0032] Figure 3 The surface metallographic morphology of the bonding surface between the outer ring of the bearing and the liner after the MAX@PTFE / Kevlar liner is peeled off in the embodiment of the present invention;
[0033] Figure 4 A schematic diagram of the surface height of the two-dimensional material @MAX@PTFE / Kevlar liner after friction and wear in an embodiment of the present invention (the color depth represents different heights, and the right side shows the height value represented by the color);
[0034] Figure 5 This is a friction and wear performance diagram of the two-dimensional material @MAX@PTFE / Kevlar liner according to an embodiment of the present invention;
[0035] Figure 6 This is a friction coefficient diagram of the two-dimensional material @MAX@PTFE / Kevlar liner after 10 hours of friction and wear experiment in an embodiment of the present invention;
[0036] Figure 7 This is a schematic diagram of the average friction coefficient of the two-dimensional material @MAX@PTFE / Kevlar liner with different mass fractions of the two-dimensional material used in the embodiment of the present invention;
[0037] Figure 8 A schematic diagram of the wear rate of the two-dimensional material @MAX@PTFE / Kevlar liner with different mass fractions of the two-dimensional material used in the embodiment of the present invention;
[0038] Fig. 9 This is a schematic diagram of the average peel strength of the MAX@PTFE / Kevlar liner using different mass ratios of catecholamine & polyvinylamine reagent mixed solutions: MAX in an embodiment of the present invention. DETAILED DESCRIPTION
[0039] In this embodiment, the two-dimensional material is molybdenum disulfide, and the liner is PTFE / Kevlar liner.
[0040] A surface treatment method for a high peel strength self-lubricating liner for a spherical bearing according to an embodiment of the present invention is carried out according to the following steps. The treatment result is as follows: Figure 1-9 As shown:
[0041] S10, selecting MAX material as reinforcing particles of the liner, dissolving the MAX material in the precursor solution, immersing the liner in the precursor solution, and drying overnight to adhere the MAX particles to the surface of the liner.
[0042] Among them, the MAX material is titanium aluminum carbide, the precursor solution is a mixed solution composed of Tris (trishydroxymethylaminomethane) buffer, deionized water, catecholamines and polyvinylamine reagents, and the mass ratio of catecholamine & polyvinylamine reagent mixed solution: MAX in the precursor solution is in the range of 8:1-2:1.
[0043] S20, performing shot peening on the bonding surface between the bearing outer ring and the liner.
[0044] The particle size of the steel shot for shot peening is 0.1-1 mm, and the shot peening pressure is 0.1-5 MPa. This selection range belongs to the conventional range, so the relevant experimental data is not provided in this embodiment.
[0045] Step S25, i.e., using the two-dimensional material to attach to the MAX@PTFE / Kevlar liner, comprises the following steps:
[0046] S25.a, diluting the adhesive with a diluent;
[0047] S25.b, adding the two-dimensional material to the mixed solution and stirring evenly;
[0048] S25.c, completely immersing the liner treated in step S10 in the solution obtained in step S25.b, so that the solution prepared in step S25.b fully penetrates the surface of the liner to obtain a two-dimensional material @MAX@PTFE / Kevlar liner;
[0049] S25.d, using a roller press to remove excess resin from the surface of the two-dimensional material @MAX@PTFE / Kevlar liner, and then drying at a temperature of 50-150°C until the surface of the two-dimensional material @MAX liner is removed and the solution obtained in S25.b remaining on the surface is removed;
[0050] S25.e, repeat steps S25.a-S25.d to increase the weight of the two-dimensional material @MAX@PTFE / Kevlar liner by 30-60%.
[0051] The adhesive in step S25.a is phenolic resin, the diluent in step S25.a is a mixed solution of ethyl acetate and anhydrous ethanol or a mixed solution of ethyl acetate, anhydrous ethanol and acetone, and the mass fraction of the two-dimensional material in step S25.b is 0.2-2%.
[0052] S30, adding adhesive between the liner and the bearing outer ring, and curing the liner and the bearing outer ring after the bonding treatment.
[0053] The curing process of step S30 is as follows:
[0054] S30.a, bonding the two-dimensional material @MAX@PTFE / Kevlar liner processed in step S25 to the surface of the bearing outer ring;
[0055] S30.b, apply 0.1-5MPa pressure and control the temperature at 150-250°C until the bonding is stable, at which point the thickness of the two-dimensional material @MAX@PTFE / Kevlar liner is 0.2-0.7mm.
[0056] In the above steps, the shot peening specific parameters and the fixed specific parameters selected in steps S20 and S30 are all related to the prior art, so this embodiment does not need to provide experimental data of the above endpoint values.
[0057] The following is a description of the experimental parameters and surface morphology used in the accompanying drawings:
[0058] Figure 1 It can be seen that after the shot peening treatment, the outer ring of the bearing has a higher surface roughness between the bonding surface of the outer ring of the bearing and the liner, which can significantly increase the contact area between the outer ring of the bearing and the two-dimensional material @MAX@PTFE / Kevlar liner.
[0059] Figure 2 It can be seen that the adhesion effect after catecholamine polymerization causes the MAX particles to agglomerate, and the particle surface is evenly wrapped by the ultra-thin co-deposition coating (i.e., the precursor liquid) and evenly distributed on the surface of the PTFE / Kevlar liner.
[0060] Figure 3 It can be seen that after the two-dimensional material @MAX@PTFE / Kevlar liner is bonded to the shot-peened bearing outer ring, the liner is peeled off using a tensile testing machine, and the peeled surface perfection of the bearing outer ring is 100%.
[0061] Figure 4-Figure 6 The friction and wear performance test process is to bond the two-dimensional material @MAX@PTFE / Kevlar liner to the outer ring of the bearing as the lower sample, and the upper sample uses a pin with a radius of 1mm. The pin material is 9Cr18Mo, and a 10-hour pin-disc test is carried out using a friction and wear testing machine.
[0062] Figure 4-Figure 5 It can be seen that after 10 hours of friction and wear test, the wear depth of the two-dimensional material @MAX@PTFE / Kevlar liner is about 73㎛.
[0063] Figure 6 It can be seen that under the experimental conditions of a load of 15 MPa and a speed of 0.081 m / s, the friction coefficient can still be stabilized at around 0.1 after a 10-hour friction and wear test.
[0064] Figure 6-Figure 9For the convenience of display, the x-axis is displayed with equal intervals. For the specific proportions, please refer to the data marked below the x-axis.
[0065] The above embodiment is only one of the preferred specific embodiments of the present invention. Common changes and substitutions made by those skilled in the art within the scope of the technical solution of the present invention are all included in the protection scope of the present invention.
Claims
1. A surface treatment method for a high peel strength self-lubricating liner for a spherical bearing, characterized in that: Follow the steps below to prepare the surface of the liner and install it on the outer ring of the spherical plain bearing. S10, selecting MAX material as reinforcing particles of the liner, dissolving the MAX material in a precursor solution, immersing the liner in the precursor solution, and drying overnight to adhere the MAX particles to the surface of the liner; S20, performing shot peening treatment on the bonding surface between the bearing outer ring and the liner; S30, adding adhesive between the liner and the bearing outer ring, and curing the liner and the bearing outer ring after the bonding treatment; There is also a step S25 between steps S20 and S30, and the step S25 includes the following steps: S25.a, diluting the adhesive with a diluent; S25.b, adding the two-dimensional material to the mixed solution obtained in S25.a above and stirring evenly; S25.c, completely immersing the liner treated in step S10 in the solution obtained in step S25.b, so that the solution obtained in step S25.b penetrates the surface of the liner to obtain a two-dimensional material @MAX liner; S25.d, using a roller press to remove excess resin from the surface of the two-dimensional material @MAX liner, and then drying at a temperature of 50-150° C. until the surface of the two-dimensional material @MAX liner is removed and the solution obtained in S25.b remaining on the surface is removed; S25.e, repeat steps S25.a-S25.d to increase the weight of the 2D material @MAX pad by 30-60%.
2. The surface treatment method of the high peel strength self-lubricating liner for spherical plain bearing according to claim 1, characterized in that: The adhesive in steps S25.a and S30 is phenolic resin; the diluent in step S25.a is a mixed solution of ethyl acetate and anhydrous ethanol or a mixed solution of ethyl acetate, anhydrous ethanol and acetone.
3. The surface treatment method of the high peel strength self-lubricating liner for spherical bearing according to claim 1, characterized in that: The mass fraction of the two-dimensional material in S25.b is 0.2-2%.
4. The surface treatment method of the high peel strength self-lubricating liner for spherical plain bearing according to claim 1, characterized in that: The curing process of step S30 is as follows: S30.a, bonding the two-dimensional material @MAX liner processed in step S25 to the surface of the bearing outer ring; S30.b, applying a pressure of 0.1-5 MPa and controlling the temperature at 150-250° C. until the bonding is stable.
5. The surface treatment method of the high peel strength self-lubricating liner for spherical plain bearing according to claim 1, characterized in that: The precursor solution in step S10 is a mixed solution composed of Tris buffer, deionized water, catecholamines and polyvinylamine reagents.
6. The surface treatment method of the high peel strength self-lubricating liner for spherical bearing according to claim 5, characterized in that: The mass ratio of the precursor solution is as follows: the mass ratio of catecholamine & polyvinylamine reagent mixed solution: MAX is in the range of 8:1-2:
1.
7. The surface treatment method of the high peel strength self-lubricating liner for spherical bearing according to claim 1, characterized in that: In the step S20, the particle size of the steel shot used for shot peening is 0.1-1 mm, and the shot peening pressure is 0.1-5 MPa.
8. The surface treatment method of a high peel strength self-lubricating liner for a spherical plain bearing according to any one of claims 1 to 7, characterized in that: The MAX material is titanium carbide aluminum.
Citation Information
Patent Citations
Methods of forming solid lubricant coatings on substrates
CN102458724A
Spherical slide bearing
JP2021110345A